Manajemen Arsip Dinamis di Sekretariat Dewan Perwakilan Rakyat Daerah (DPRD) Kota Binjai - Nurmala Lubis; Abdul Karim Batubara; M. Nasihudin Ali (Journal Innovation In Education, 2024)
This research was conducted at the Secretariat of the Regional People's Representative Council (DPRD Kota Binjai). The purpose of this research is to find out about how archives are created, used and maintained as well as dynamic archive management constraints so that they can be used according to their functions in the Binjai City DPRD. The research method used is descriptive qualitative. This study intends to reveal the phenomena that exist in the field, namely: how to create archives, use and maintain archives and what constraints are faced in archives management. Furthermore, researchers conducted interviews with 3 staff members of the Administration General Section of the Binjai City DPRD Secretariat. research shows that the creation of archives has not been maximized, the Human Resources of the DPRD Kota Binjai have not been optimal in the use and maintenance of archives, there is no person in charge/special officer who handles incoming and outgoing letters up to the archiving stage, archive storage is still done manually, in storage, archives are stored based on the year of the archive so as to make it less optimal and inefficient in the efficiency of the archive, resulting in the archive not functioning according to its function in terms of creating and using and maintaining the archive.